Twin-twin transfusion syndrome: a literature review - Marcio Erlei Vieira de Sa Filho; Rafael Lauro Silva Lima; Fredson Guilherme Gomes (Revista Médica de Minas Gerais, 2022)
Twin-twin transfusion syndrome is a complication of monochorionic twin pregnancies. In addition to commonly occurring in the second trimester, it has high fetal and neonatal morbidity and mortality and incidence rates ranging from 10 to 15% among all monochorionic pregnancies. This study aims to perform a literature review based on a bibliographic survey about the main epidemiological, clinical and therapeutic aspects of TTTS. The PubMed database was consulted, as the search terms used were "twin-twin transfusion syndrome", "diagnosis", and "treatment". Sixty-eight literature review and systematic review articles were obtained, and only twenty-nine were selected after applying the eligibility criteria. About the pathophysiology, the syndrome is explained by direct blood transfer between the twin fetuses through placental arteriovenous anastomoses, determining the existence of a recipient fetus and another donor. Although pregnant women are usually asymptomatic, the clinical fetal repercussions are often severe. Diagnosis is exclusively ultrasonographic and must be made as early as possible, emphasizing the importance of detecting chorionicity in twin pregnancy, in addition to serial ultrasonographic follow-up to track the development of the syndrome. Although there is still no well-established treatment protocol, endoscopic laser ablation of vascular anastomoses is considered the gold standard among the available therapeutic options. It has a high survival rate for at least one of the fetuses and low rates of neonatal neurological sequelae and can only be performed until the 26th week of pregnancy.